Effect of penetration depth and particle size on detection of wheat flour adulterant using hyperspectral imaging. (April 2021) - Fu, Xiaping; Chen, Jinchao; Zhang, Jianyi; Fu, Feng; Wu, Chuanyu
Abstract : Near-infrared (NIR) hyperspectral imaging is a useful method for powdery food quality and safety evaluation. Due to the particularity of the powder, light penetration depth and adulterant particle size have an effect on detection of adulterants in wheat flour. In this study, wheat flour of different thickness was placed on talcum powder or benzoyl peroxide (BPO) of different particle sizes to study the light penetration depth. BPO of different particle sizes was also mixed in wheat flour to study the adulterant particle size effects. The results showed that, for talcum, the light penetration depth in wheat flour was 0.6 mm, and for BPO, the light penetration depth in wheat flour was 0.8–1 mm (depending on the particle size of BPO). In terms of the particle size effects, mixtures of wheat flour and BPO with particle sizes of 380–270 μm and 270–250 μm were found to have better adulterant detection results. It indicated that the difference of particle size of subsurface reference powder would affect the light penetration depth. Combined with the ideal "multi-layer effect" hypothesis, it is verified that the penetration depth of light and the particle size of adulterant affect the detection of adulterant in wheat flour. Highlights: The "multi-layer effect" can explain the results for powder adulterant discrimination. The difference of subsurface reference powder affects the light penetration depth. BPO particle size close to the camera spatial resolution has a better detection result.